Perception of Dialect Variation by Young Adults with High-Functioning Autism. - Clopper, Cynthia; Rohrbeck, Kristin; Wagner, Laura (Journal of Autism & Developmental Disorders, 2012)
The linguistic profile of people with Autism spectrum disorders typically involves intact perceptual processing, accompanied by deficits in the social functions of language. In a series of three experiments, the impact of this profile on the perception of regional dialect was examined. Young adults with High-Functioning Autism exhibited similar performance to a typically developing comparison group in regional dialect classification and localness rating tasks, suggesting that they can use indexical information in speech to make judgments about the regional background of unfamiliar talkers. However, the participants with High-Functioning Autism were less able to differentiate among the dialects in a language attitudes task, suggesting that they do not share social stereotypes related to dialect variation with the typically developing comparison group.